Education and Health Services in Uganda : Quality of Inputs, User Satisfaction, and Community Welfare Levels - Tsimpo, Clarence; Etang, Alvin; Wodon, Quentin (World Bank, Washington, DC, 2017)
Good health and quality education are essential for economic growth and poverty reduction. Unfortunately, the quality of the education and health services provided in low-income countries is often low. Improving access and quality of education and health are key policy goals for Uganda. This paper builds on the Service Delivery Indicator study by further exploring issues related to the quality of service delivery in Uganda. The paper analyzes the quality of service from a poverty perspective, to contribute to the ongoing policy debate on the quality of service delivery in Uganda, especially in the education and health sectors. Combining data from the Service Delivery Indicator and the Uganda National Household Survey surveys, the paper shows a strong correlation between welfare and quality of service. The quality of service is lowest for those living in poor areas. This has implications for pupils' learning outcomes. Pupils in poor areas perform poorly on a standardized test covering English, numeracy, and nonverbal reasoning. Increased access to education was not accompanied by improvement in learning outcomes. Results from econometric analysis suggest that improvements in school facilities, improvements in the quality of teaching, and the knowledge base of teachers could bring substantial gains in student performance, particularly in poor communities. Despite the low quality they face, if the poor are more satisfied with the service, this has implications for demand for social accountability, as the poor often are not exposed to or ignore the standard of service to which they should refer.